PENGARUH ORGANIZATIONAL CLIMATE TERHADAP KINERJA ORGANISASI YANG DIMEDIASI OLEH INNOVATIVE WORK BEHAVIOR PADA BANK BNI KANTOR CABANG UTAMA BANDA ACEH - Teuku Hilham Fajar; Ade Irma Suryani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to examine the influence of the Organizational Climate on Organizational Performance with the Innovative Work Behavior as a mediating variable at BNI Bank, Banda Aceh Main Branch Office. The sample used in this study were 71 employees of BNI Bank Banda Aceh Main Branch Office using total sampling technique. This study, (questionnaire) to collect data. Hierarchical Linear Modeling (HLM) is used in this study as the method of data analysis to determine the effect of the variables involved and Sobel Test is used to test the mediating effect. Based on the results of the HLM analysis and Sobel test, it shows that Organizational Climate and innovative work behavior have positive effect on Organizational Performance. Organizational Climate has a positive effect on Innovative Work Behavior, Innovative Work Behavior partially mediates the relationship between Organizational Climate and Organizational Performance.